Daycare Subsidies and Labor Supply in Sweden - Siv Gustafsson; Frank Stafford (The Research Institute of Industrial Economics (IUI), 1989)
This paper utilizes data from a Swedish household survey for 1984 (The HUS data) in combination with data on public daycare fees and spaces per child by community. We argue that the subsidy rate and availability of spaces determined by the political leaders of the community is to a large extent exogenous to the household. The joint out-of-home childcare and labor supply decision is analyzed by logit choice models. We find that the high quality public daycare in Sweden encourages labor market activity of women with preschoolers even when spouse's income is high and that when spaces are not rationed a lower price encourages use.
Keywords: H31; H53; J22; 330; Childcare subsidies; labour supply; community provision of services